Depression comorbidity in epileptic rats is related to brain glucose hypometabolism and hypersynchronicity in the metabolic network architecture. (30th March 2018) - Zanirati, Gabriele; Azevedo, Pamella Nunes; Venturin, Gianina Teribele; Greggio, Samuel; Alcará, Allan Marinho; Zimmer, Eduardo R.; Feltes, Paula Kopschina; DaCosta, Jaderson Costa
Summary: Objective: Temporal lobe epilepsy (TLE) is one of the most common types of epilepsy syndromes in the world. Depression is an important comorbidity of epilepsy, which has been reported in patients with TLE and in different experimental models of epilepsy. However, there is no established consensus on which brain regions are associated with the manifestation of depression in epilepsy. Here, we investigated the alterations in cerebral glucose metabolism and the metabolic network in the pilocarpine‐induced rat model of epilepsy and correlated it with depressive behavior during the chronic phase of epilepsy. Methods: Fluorodeoxyglucose ( 18 F‐FDG) was used to investigate the cerebral metabolism, and a cross‐correlation matrix was used to examine the metabolic network in chronically epileptic rats using micro–positron emission tomography (microPET) imaging. An experimental model of epilepsy was induced by pilocarpine injection (320 mg/kg, ip). Forced swim test (FST), sucrose preference test (SPT), and eating‐related depression test (ERDT) were used to evaluate depression‐like behavior. Results: Our results show an association between epilepsy and depression comorbidity based on changes in both cerebral glucose metabolism and the functional metabolic network. In addition, we have identified a significant correlation between brain glucose hypometabolism and depressive‐like behavior in chronically epileptic rats. Furthermore, we found that the epileptic depressed group presents a hypersynchronous brain metabolic network in relation to the epileptic nondepressed group. Significance: This study revealed relevant alterations in glucose metabolism and the metabolic network among the brain regions of interest for both epilepsy and depression pathologies. Thus it seems that depression in epileptic animals is associated with a more diffuse hypometabolism and altered metabolic network architecture and plays an important role in chronic epilepsy.